Optimum Time Schedule for Industrial Processes (II) - Makky, S.M.; Othman, Y.M . (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The  present study  deals  with successive  stages  of  productiveoperations happened to produce a production within each stage befo re it  moves to the next one. ll cou ld  be deduced that this study is an extension  to what bas  been mentioned  in (1 ) .ln  (I),  the  optimum distribution of  di!Terent jobs of  workers and  machines  in  the productive operations has been st ud ied whi le the study  invol ves the optimum schedule for the succession of these operations presuming that thay have already been distributed on machines and workers (2).A mathematical form has been put for this study to define the "Object.ive Function " where the total work could be performed in the shortest time.The incapability of tackling two works at same time by the workersand machines,  and the inabi lity of beginning a new stage before the end of the precedi ng one, both were taken i nto consideration  . These conditions were put in such mathematical forms as - conditions - for the - Optimization Problem -.The above mentioned operation was gcnerall y fonned  where iL   :an be  applied  lor  the optimum schedule  to  pursue operations  in  theproductive ones.Then,  the virtual  application  in  printing which  has  already  beendisplayed  in (I) as a  sample for  the optimum distribution  in  the productive operations.The data gained in (I) "ere used as (inputs ) for the problem being solved.